Implementasi Kebijakan Akreditasi Puskesmas dalam Meningkatkan Kualitas Pelayanan Kesehatan di Kota Denpasar - Ni Komang Asri Novitasari; Toto Noerasto (Public Inspiration : Jurnal Administrasi Publik, 2025)
Community Health Centers (Puskesmas) play a strategic role as the frontline of primary healthcare services in improving the quality of public health services. Denpasar City is one of the regions that has successfully achieved Paripurna accreditation for all its Puskesmas, making it a model for successful accreditation policy implementation. This study aims to analyze and describe the implementation of the Puskesmas accreditation policy in Denpasar City and identify the supporting and inhibiting factors in the process. The research approach uses a qualitative descriptive method, applying George C. Edward III's policy implementation theory, which includes four main factors: communication, resources, disposition, and bureaucratic structure. Data collection was conducted through observation, in-depth interviews, and documentation studies. Informants were selected using purposive sampling, and qualitative data analysis was inductive. The results show that the implementation of the accreditation policy in Denpasar City has shown progress, but several challenges remain. Supporting factors include effective communication between Puskesmas and the Health Office, adequate human resources, high staff commitment, and an organized bureaucratic structure. On the other hand, inhibiting factors include budget limitations, uneven workload distribution, a lack of shared understanding among staff, and suboptimal task division. This study recommends increased socialization, continuous training, and restructuring of the bureaucratic framework to strengthen the implementation of the accreditation policy.